Alleviation of glutamate mediated neuronal insult by piroxicam in rodent model of focal cerebral ischemia: a possible mechanism of GABA agonism - Bhattacharya P.; Pandey A.K.; Paul S.; Patnaik R. (My University, 2025)
Neurotransmitter imbalance is an inevitable outcome in cerebral ischemia that leads to neuronal death. In the present study, we evaluated the effects of piroxicam, a nonsteroidal anti-inflammatory drug (NSAID), on extracellular brain glutamate and γ-aminobutyric acid (GABA) release, survival time, and neuronal cell death. Transient focal cerebral ischemia in male Charles Foster rat led to neuronal infarction and compromised intrinsic antioxidant status. Thirty-minute preadministration of piroxicam (10 mg/kg b.w.) showed a significant (P < 0.01) reduction in cerebral infarct volume and potentiation of the intrinsic antioxidant status. High-performance liquid chromatography of brain cortex and striatum revealed changes in extracellular concentrations of neurotransmitters which were found to be 0.519 ± 0.44 pmole/mg (GABA); 1.18 ± 0.28 pmole/mg (glutamate), and 0.63 ± 0.21 pmole/mg (serotonin), respectively. Hydroxyl radical (·OH) adduct of salicylate in the frontal cortex and striatum in control, untreated, and treated groups was found to be 0.261 ± 0.06, 0.68 ± 0.52, and 0.401 ± 0.68 pmole/mg, respectively. After stroke, the extracellular level of glutamate in rat brain increases continuously as compared to that of control group. However, piroxicam administration in stroke rat significantly reduced (P < 0.05) elevated extracellular cerebral glutamate. This indicates that piroxicam attenuates extracellular glutamate release and also reduces neuronal cell death due to reduction in oxidative stress in cerebral ischemia. Our results also indicate a consequent increase of extracellular GABA in brain regions administered with piroxicam, which hints that piroxicam alleviates glutamate excitotoxicity possibly by GABA agonism. © 2014, University of Navarra.